Geotechnical Analysis in the Case of Recovery Failure of West Out Pit Dump PT. Mifa Bersaudara - Rezky, Danu; Khomeini, Andi Ronald; Balyani, Kiagus Farobi (UIR PRESS, 2025)
The formation of waste dump with heterogeneity of constituent materials and muddy Base conditions as the foundation of the waste dump is a challenge for practitioners and academics so that stable embankments as a place to dispose of overburden material can be formed. Case studies that occurred at PT. Mifa Bersaudara, namely the Failure of West Out Pit Dump (OPD) Elevation +30 to elevation +15 which caused the Water Monitoring Point (WMP 24) to be damaged and potentially damage the IUP boundary road. This incident occurred through Prism monitoring and the loss of the progressive movement category which caused the disposal of elevation +30 to be sterilized from dumping operations before recovery disposal was carried out. The Back Analysis Approach, Laboratory Testing, and tracing of dumping history were carried out to obtain accurate material model and property analysis. Geotechnical recommendations start from the reconstruction of the Water Monitoring Point by re-filling the failure area at elevation +20 and the compartment embankment at elevation +23. After that, it was continued with the reconstruction of the disposal leg (counterweight) elevation +25, as well as adjusting the geometry of the disposal elevations +30, +40, and +50 so that the failure area could be re-filled. The final results obtained from this case study are that the IUP boundary road and Water Monitoring Point were successfully constructed, Optimization of disposal in the failure area can be done by adding a volume of 1.3 million bcm, and the recovery area for the failure of disposal can be used as a reclamation area with an area of ​​4 Ha. The update of the Safety Factor value after the work stated that the disposal was in a Safe condition. Description of Recommendations, Staging Plan, and future research development will be explained further in this Paper.